Detecting Communities in Science Blogs - Pikas, C.K. (2008 Fourth IEEE International Conference on EScience, 2008)
Many scientists maintain blogs and participate in online communities through their blogs and other scientists' blogs. This study used social network analysis methods to locate and describe online communities in science blogs. The structure of the science blogosphere was examined using links between blogs in blogrolls and in comments. By blogroll, the blogs are densely connected and cohesive subgroups are not easily found. Using spin glass community detection, six cohesive subgroups loosely corresponding to subject area were found. By commenter links, the blogs form into more easily findable general subject area or interest clusters.